Navigating fashion: On the role of digital fashion archives in the preservation, classification and dissemination of fashion heritage. Issue 1 (1st June 2019) - Franceschini, Marta
Digital platforms propose themselves to be repositories of objects, translating the actual archive into a digital architecture made of files and data. However, in becoming digital data, the very materiality of fashion objects changes, leading to the formation of structures that preserve and organize these objects. This article considers digital archives dealing with fashion, aiming to capture the nuances of the digitization and opening up of collections in relation to definitions of the fashion archive and of fashion itself. It looks at the ways in which institutions dealing with fashion heritage have relied on digital technologies to archive data and make them available to wider audiences. The article does this through the examination of three case studies: Open Fashion, the platform developed by fashion museum MoMu (ModeMuseum Provincie Antwerpen) in Antwerp, together with Artesis Hogeschool Antwerpen; Europeana Fashion, a platform gathering digital data linked to fashion heritage from more than thirty institutions around Europe; and the Digital Archive of Armani/Silos, a corporate archive open to the public but searchable only from within the exhibition space in Milan. These three projects will first be described, then their digital platforms and strategies will be analysed in order to evaluate both their positive aspects and the risks involved in setting up and maintaining these digital depots. Ultimately, the main objectives of the article are to evaluate both the spaces and the boundaries that these archives have created and to understand the ways in which access generated by digitization channels either enables or restricts interpretation of fashion objects.